Microbial Biopesticides to Control Whiteflies in Eggplant Solanum melongena, in Greenhouse - Héctor Cabrera-Mireles; Magali Jiménez-Jiménez; Juan Ruiz-Ramírez; Félix David Murillo-Cuevas; Jacel Adame-García; Jorge Jiménez-Zilli; Andrés Vásquez Hernández; Rubén Uriel Herrera-Bonilla (Insects)
The whitefly is among the main pests of crops, especially solanaceous and cucurbitaceous plants. The massive use of pesticides for its control has led to an increase in the pest’s resistance to different groups of insecticides and to environmental contamination. The use of biopesticides for its control is a sustainable alternative for the environment. The objective of this study was to evaluate the efficiency of two biopesticides based on entomopathogenic fungi against eggs, nymphs, and adults of whitefly in eggplant in a greenhouse. The treatments consisted of Cordyceps javanica, Beauveria bassiana, a commercial insecticide (i.e., Spirotetramat), and a control (no application). A completely randomized design was used with 16 repetitions per treatment, and the non-parametric Kruskal–Wallis test was applied. Mortality was recorded on five dates after application (DAA). The sampling data were transformed to efficiency (%). The biopesticides were found to be effective in controlling whiteflies in all developmental stages during the evaluation days.